Personality traits, role ambiguity, and relational competence as predictors for teacher subjective wellbeing - Macovei, Crenguța Mihaela; Bumbuc, Ștefania; Martinescu-Bădălan, Fabiana (Frontiers in Psychology, 2023)
The coronavirus pandemic has significantly reshaped the way teaching activities are carried out, thus intensifying the stress felt by teachers. The teacher-student relationship has also changed under the influence of social constraints. Together, these have affected teachers’ work efficiency and redefined their connection with the school. The present study aims to examine the extent to which personality traits, role ambiguity, and relational competence predict teacher subjective wellbeing. The study sample consisted of 105 university teachers. Three hierarchical multiple regression analyses were conducted separately for each of the three criterion variables used in this research: teaching efficacy, school connectedness and teacher subjective wellbeing. The results indicated that the personality traits emotionality, extraversion and conscientiousness are significant predictors for all three variables, while honesty-humility, agreeableness and openness to experience are not predictors for any of the variables. However, in the third step of the regression analysis, conscientiousness was found to lose its predictive quality for the variables school connectedness and teacher subjective wellbeing, its place being taken by emotionality. Both role ambiguity and relational competence are significant predictors for teaching efficacy, for school connectedness and also for teacher subjective wellbeing.